Трипс бегонієвий (Thysanoptera: Thripidae) в оранжереях Ботанічного саду імені акад. О.В. Фоміна та заходи управління його чисельністю - Chumak, P.Ya. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2013)
The data of resistance of begonia to the Scirtothrips longipennis Bagnall are given. The ecologically safe method of plant protection from this pest is described.